IMPLEMENTASI PENGGUNAAN DANA DESA PADA MASA PANDEMI COVID-19 DI DESA BARU TAHAN TAHUN 2020 - Vivin Fitryani; Marisa Sutanty; M Mulyasih (Pusat Riset dan Publikasi, 2021)
This study aims to describe the use of the Village Fund for the 2020 fiscal year in handling covid-19 in the Barutahan Village, including the use of the Village Fund for the use of BLT-DD, prevention and handling of covid-19, village cash labor intensive prioritized for community needs during the pandemic. The purpose of this study was to find out the extent of the implementation of the use of village funds during the covid-19 pandemic in the Baru Tahan Village. The data used are primary data and secondary data. This research uses a qualitative descriptive method. The type of data in this study is qualitative data. Data were analyzed using Miles Huberman interaction. The results showed that the use of Village Funds for covid-19-Free Villages, used for BLT-DD, prevention and handling of covid-19, and the village cash-intensive work in Desa Baru Tahan was in accordance with the Permendes which Village Funds were designated for handling covid-19.